2022
DOI: 10.1177/23259671221132555
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Knee Dislocation With Primary Repair and Suture Augmentation: A Viable Solution

Abstract: Background: Different surgical techniques have been described for the treatment of knee dislocation (KD). Nonoperative approaches are frequently combined with surgical reconstruction using auto- or allograft. Purpose: To evaluate the midterm results of primary surgical repair and suture augmentation to treat KD. Study Design: Case series; Level of evidence, 4. Methods: A total of 22 patients (5 women, 17 men; mean age, 45 ± 15 years) with KD were evaluated at a mean of 49 ± 16 months after surgical treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…As described by Malik et al [ 8 ], most of them occurred through a posterolateral displacement, and according to the Schenck classification, they start from KD IIIM as a grade of severity [ 12 , 14 , 28 ]. With KD type III reported as the most common type in the entire KD literature, this systematic review agrees since KD III was the major injury pattern described [ 4 , 12 , 14 , 28 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…As described by Malik et al [ 8 ], most of them occurred through a posterolateral displacement, and according to the Schenck classification, they start from KD IIIM as a grade of severity [ 12 , 14 , 28 ]. With KD type III reported as the most common type in the entire KD literature, this systematic review agrees since KD III was the major injury pattern described [ 4 , 12 , 14 , 28 ].…”
Section: Discussionsupporting
confidence: 83%
“…IKDs represent a unique, rare rotatory subcategory of KDs [ 1 4 , 7 , 8 , 10 , 28 ]. As described by Malik et al [ 8 ], most of them occurred through a posterolateral displacement, and according to the Schenck classification, they start from KD IIIM as a grade of severity [ 12 , 14 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While conservative treatment showed inferior results, primary stabilisation of highly unstable knee joints with an external fixator or primary ligament bracing showed significantly better results [9,12,15,24]. A meta-analysis published by Frosch et al comparing ligament bracing and reconstruction of the ACL and/or PCL showed comparable results, including dislocation of Schenck II and higher dislocations [4].…”
Section: Discussionmentioning
confidence: 99%